1994
DOI: 10.1093/infdis/170.4.775
|View full text |Cite
|
Sign up to set email alerts
|

Cd8+ Lymphocyte Activation At Human Immunodeficiency Virus Type 1 Seroconversion: Development Of Hla-Dr+ Cd38- Cd8+ Cells Is Associated With Subsequent Stable Cd4+ Cell Levels

Abstract: Subsets of activated CD8+ lymphocytes defined by membrane expression of the activation antigens HLA-DR and CD38 were counted by three-color flow cytometry in homosexual men who subsequently became seropositive for human immunodeficiency virus type 1 (HIV). Profound CD8+ cell activation was seen in all subjects at seroconversion and 6 and 12 months later. The HLA-DR+ CD38+ CD8+ cell population, which has potent direct HIV cytotoxic T cell activity, was markedly elevated at seroconversion in all subjects. In som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
93
0
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(105 citation statements)
references
References 23 publications
10
93
0
2
Order By: Relevance
“…The opposite was true for resting T cell subsets. The observation that CD8 þ T cells expressing only HLA-DR but not CD38 are lost in Ethiopian AIDS patients is in agreement with a previous prospective study which demonstrated that the presence of this subset is associated with long-term survival and stable CD4 þ T cell counts [14]. Apart from being an activation marker, CD38 is also detected in immature cells [43].The representation of CD4 þ and CD8 þ T cells expressing only CD38 but not HLA-DR is increased in both HIV þ and AIDS groups compared with the HIV ¹ group.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The opposite was true for resting T cell subsets. The observation that CD8 þ T cells expressing only HLA-DR but not CD38 are lost in Ethiopian AIDS patients is in agreement with a previous prospective study which demonstrated that the presence of this subset is associated with long-term survival and stable CD4 þ T cell counts [14]. Apart from being an activation marker, CD38 is also detected in immature cells [43].The representation of CD4 þ and CD8 þ T cells expressing only CD38 but not HLA-DR is increased in both HIV þ and AIDS groups compared with the HIV ¹ group.…”
Section: Discussionsupporting
confidence: 92%
“…Activated and resting T cell subsets were measured using a combination of HLA-DR and CD38 MoAbs, as described [12,14]. Figure 1c, …”
Section: Activated and Resting T Cell Subsets In Ethiopian Hiv ¹ Himentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have demonstrated that suppressed viral replication is followed by decreased immune activation, increased expression of co-stimulatory molecules, and increased numbers of naive circulating T cells. 1 ± 9 Other studies indicate that abnormal T cell activation occurs in HIV infection, 42,43,50,51 and that this abnormality increases susceptibility of T cells to become infected, 52 ± 54 or to die by apoptosis. 35,55,56 The abnormal state of activation may therefore be central to the pathogenesis of HIV disease.…”
Section: Immune Reconstitution Following Therapymentioning
confidence: 99%
“…PD-1 and HLA-DR serve as activation markers of lymphocytes, associated with persistent antigen exposure [24,25] and have been implicated in both activation [26] and exhaustion of CD8 1 T cells in HIV infection [27][28][29]. NK cells in the LNs of HIVindividuals expressed elevated frequencies of HLA-DR (Fig.…”
Section: Nk Cells In Lns Are Highly Activatedmentioning
confidence: 99%